2016
DOI: 10.1620/tjem.238.57
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the Glutathione-S-Transferase P1 Gene Promoter Is Associated with Oxidative Stress in Patients with Chronic Hepatitis B

Abstract: Glutathione-S-transferase P1 (GSTP1) and glutathione-S-transferase M3 (GSTM3) catalyze the glutathione-related clearance of xenobiotics. The methylation of these gene promoters was associated with oxidative stress that induced liver damage. This study aims to explore the relationship among GSTP1 and GSTM3 methylation, DNA methyltransferases (DNMTs) expression, and oxidative stress in patients with chronic hepatitis B (CHB). We retrospectively enrolled 153 patients with CHB and 40 healthy controls (HCs). The GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…A dysfunction of the mitochondrial antioxidant system may render mitochondria susceptible to injuries despite the adequate cytosolic antioxidant levels ( Cano et al, 2014 ). Viral infections were shown to induce mitochondrial damage and oxidative stress ( Acar et al, 2009 ; Khadem Ansari et al, 2015 ; Fan et al, 2016 ), which was confirmed in this study as well, since the SOD activity was shown to decreased while MDA concentrations increased in HEV-infected groups. Our combined results support the conclusion that HEV infection induces mitochondrial damage, which leads to oxidative stress development.…”
Section: Discussionsupporting
confidence: 86%
“…A dysfunction of the mitochondrial antioxidant system may render mitochondria susceptible to injuries despite the adequate cytosolic antioxidant levels ( Cano et al, 2014 ). Viral infections were shown to induce mitochondrial damage and oxidative stress ( Acar et al, 2009 ; Khadem Ansari et al, 2015 ; Fan et al, 2016 ), which was confirmed in this study as well, since the SOD activity was shown to decreased while MDA concentrations increased in HEV-infected groups. Our combined results support the conclusion that HEV infection induces mitochondrial damage, which leads to oxidative stress development.…”
Section: Discussionsupporting
confidence: 86%
“…Air pollution exposure generates reactive oxygen species (ROS) and the resulting oxidant imbalance is thought to be a central pathway mediating the association between air pollution exposure and impaired lung function [ 42 , 43 ]. GSTP1 controls enzymes involved in the detoxification of ROS [ 44 ] - GSTP1 variants are more susceptible to the health effects of air pollution, including lung function, [ 45 ] and GSTP1 methylation is associated with oxidative stress [ 46 ]. The developing fetus is especially prone to oxidative injury, as antioxidant defenses remain immature through pregnancy; male fetuses may be at even increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FSHR is selectively expressed in Sertoli cells and ovarian granulosa cells (Camp, Rahal, & Mayo, ; Dankbar et al, ), and its expression level is closely related to germ cell differentiation and maturation (Heckert & Griswold, ). Gene promoters play a significant role in transcriptional regulation (Fan et al, ; Wang et al, ). At present, the FSHR promoter of humans, rats, mice and sheep has been successfully cloned (Gromoll, Dankbar, & Gudermann, ; Heckert, Daley, & Griswold, ; Levallet, Koskimies, Rahman, & Huhtaniemi, ; Sairam & Subbarayan, ), and the mechanism of transcriptional regulation has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%